WireSafeTM – A pilot study of a novel safety engineered device designed to prevent guidewire retention and reduce sharps injuries during central venous catheter insertion. (May 2023) - Patel, Vikesh; Chemban, Faiz M; Samad, Sohel; Swan, Thomas; Gooch, James; Dean, Jonathan; Pearson, Darcy; Heij, Robin; Young, Peter J; Mariyaselvam, Maryanne ZA
Background: Guidewire retention and sharps injury during central venous catheter insertion are errors that cause patient and healthcare professional harm. The WireSafe TM is a novel procedure safety pack engineered to prevent guidewire retention and sharps injury during central venous catheter insertion. This is a pilot study aimed to determine its acceptability, usability and safety during clinical practice. Methods: An observational time and motion study was conducted comparing central venous catheter insertion and sharps disposal practice using standard versus WireSafe TM techniques. One-year following implementation, a structured survey was conducted to determine clinician opinion and experiences of using the WireSafe TM . Results: 15 procedures were observed using standard practice and 16 using the WireSafe TM technique. The WireSafe TM technique decreased the time taken from removal of the guidewire to disposal of sharps (standard 11.4 ± 5.6 min vs WireSafe TM 8.7 ± 1.4 min, p = 0.035), as well as total procedure time (standard 16 ± 7 min vs WireSafe TM 14.2 ± 2 min, p = 0.17), although this latter trend did not reach significance. Clinicians frequently practiced unsafe behaviour during sharps disposal in the standard group (53%), but when using the WireSafe TM technique, 100% exhibited safe practice by transferring sharps to the bin inside the sealed WireSafe TM box. One-year following implementation, 20 clinicians participated in the structured survey. Clinicians across three different departments used the WireSafe TM in varying clinical situations and reported that its use for central line insertion was either easier (10/20) or no different (10/20) compared to standard practice. All clinicians (20/20) felt that the WireSafe TM reduced the risk of guidewire retention and all stated that they approved of the WireSafe TM technique, and supported its use for convenience and safety benefits. Conclusion: Utilising the WireSafe TM for central line insertion facilitated earlier and safer sharps disposal, and the device was well supported by clinicians for its convenience and safety benefits.